Prospective evaluation of antibody response to Streptococcus gallolyticus and risk of colorectal cancer - Butt, J; Jenab, M; Willhauck-Fleckenstein, M; Bradbury, K; al., E (Wiley, 2018)
The gut microbiome is increasingly implicated in colorectal cancer (CRC) development. A subgroup of patients diagnosed with CRC show high antibody responses to Streptococcus gallolyticus subspecies gallolyticus (SGG). However, it is unclear whether the association is also present pre-diagnostically. We assessed the association of antibody responses to SGG proteins in pre-diagnostic serum samples with CRC risk in a case-control study nested within a prospective cohort. Pre-diagnostic serum samples from 485 first incident CRC cases (mean time between blood draw and diagnosis 3.4 years) and 485 matched controls in the European Prospective Investigation into Nutrition and Cancer (EPIC) study were analyzed for antibody responses to eleven SGG proteins using multiplex serology. Odds ratios (OR) and 95 % confidence intervals (CI) were estimated using multivariable conditional logistic regression models. Antibody positivity for any of the eleven SGG proteins was significantly associated with CRC risk with 56% positive controls compared to 63% positive cases (OR: 1.36, 95% CI: 1.04-1.77). Positivity for two or more proteins of a previously identified SGG 6-marker panel with greater CRC-specificity was also observed among 9% of controls compared to 17% of CRC cases, corresponding to a significantly increased CRC risk (OR: 2.17, 95% CI: 1.44-3.27). In this prospective nested case-control study we observed a positive association between antibody responses to SGG and CRC development in serum samples taken pre-diagnostically. Further work is required to establish the possibly etiological significance of these observations and whether SGG serology may be applicable for CRC risk stratification.